PF.24 The PLUTO Study: Evaluation of the Cost-Effectiveness of Percutaneous Vesicoamniotic Shunting (VAS) For Lower Urinary Tract Obstruction (LUTO). (26th April 2013) - Diwakar, L; Morris, RK; Malin, GL; Barton, PM; Roberts, TE; Kilby, MD
Abstract : Objective: To determine the cost-effectiveness of VAS for LUTO compared to conservative management. Design: A model based economic evaluation based on a decision tree utilising data from the RCT. Deterministic and probabilistic sensitivity analyses were performed. Setting: Fetal Medicine departments (England, Scotland, Ireland, Netherlands). Participants: Pregnant women with singleton, male fetus with isolated LUTO. Main Outcome Measures: Incremental health care costs (ICER) - cost per additional survivor at 28 days; cost per survivor at one year; cost of disability free survival. Results: Insertion of VAS incurred an additional cost of £15, 500 per survivor at 1 year, additional cost per disability free life year £43, 900. Average healthcare costs for VAS were £21, 000 compared to £9, 900 for conservative therapy, additional costs occurred mainly through additional surgery and intensive care costs. The ICER per additional survivor at 28 days was estimated as £15, 500 and per survivor at one year as £15, 400. Taking into account the poor health of many of those who did survive, the ICER per disability free life year with VAS was much higher at about £43, 900. Taking account of the uncertainty in data, the ICER could be much higher and thus VAS may be both more costly and less effective than conventional treatment. Conclusion: The health economic analysis suggests that the costs associated with this small gain in disability free life years in the first year of life are high, and are unlikely to be judged cost-effective. Much depends on the long-term survival of those who have reached 1 year.